3D Motion Analysis for the Assessment of Dynamic Coupling in Transtibial Prosthetics: A Proof of Concept - Sean Cullen; Ruth Mackay; Amir Mohagheghi; Xinli Du (IEEE Open Journal of Engineering in Medicine and Biology, 2023)
Assessment of coupling between transtibial sockets and users is historically based on clinicians’ observations and experience, but can be inaccurate and unreliable. Therefore, we present a proof of concept, for five out of six possible degrees of freedom coupling metric system for a socket, using motion analysis calibrated on a 3D printed limb substitute. The method is compatible with any socket suspension method and does not require prior modifications to the socket. Calibration trials were used to locate the axis of rotation of the knee joint referenced against a marker cluster on the thigh; this allowed for the identification of the limb during test trials despite the entire residuum being obscured from view by the socket. The error in the technique was found to be within 0.7 mm in displacement and 0.7 degrees in rotation, based on the control data. Dynamic testing showed the Inter Quartile Range (IQR) of inter time step variance was <0.5 mm/deg for all metrics. The method can form a basis for objective socket evaluation, improve clinical practice and the quality of life for amputees.